Investigation On Overcurrent Relay Setting And Performance Using PSCAD Software - Hairi, Mohd Hendra; Mohd Isira, Ahmad Sadhiqin; Kamarudin, Muhammad Nizam; Packeer Mohamed, Mohamed Fauzi (Universiti Teknikal Malaysia Melaka, 2021)
This paper presents a study on overcurrent relay setting and performance at 132/33/11kV Hutan Melintang network, Teluk Intan, Perak, Malaysia radial distribution feeder. The study involves an investigation on the existing setting on overcurrent relay and performance. This study includes checking the appropriate relaying Plug Setting (PS) and Time Multiplier Setting (TMS) for the discrimination process. The IEEE std. C37.112 moderately inverse IDMT curve characteristic is chosen for the simulation using the Power System Computer-Aided Design (PSCAD). The result shows that the existing PSM and TMS are well-chosen, and the relay performance is in good condition